861 Debrief sessions for staff involved in child safeguarding. (17th August 2022) - Jayesinghe, Ryan; Busari, Temitope; Bentwood, Sara; Helps, Sarah; Osborne, Sarah
Abstract : Aims: The difficulties faced by health care professionals involved in child safeguarding can negatively impact their physical and mental health 2 . Literature research revealed that 'debrief sessions' have empirically improved mental wellbeing and performance. 3, 4 This project aimed to 1) Implement and assess the effectiveness of safeguarding debrief sessions, 2) Gauge if nursing staff would benefit from debrief sessions. Methods: Beginning March 2021, monthly virtual debrief sessions on difficult cases were discussed with King's College Hospital staff, who were involved in challenging child safeguarding scenarios. A post-session questionnaire was issued to assess session utility. A second questionnaire, December 2021, was also sent to specialist Safeguarding nurses who engaged in the sessions and dealt with difficult safeguarding cases to gauge their interest in further debrief sessions. Results: There were seven responses to the March/April questionnaire. Although participants found the session moderately helpful and felt listened to too, the results indicated that the session failed to help staff manage challenging situations, nor did it provide tools to use in future cases. A prevailing theme was staff had different expectations of the session, and the virtual environment was not conducive to a useful session. Nine nursing staff responded to the second questionnaire, 8 of whom agreed the debrief sessions would be beneficial. Conclusion: In conclusion, debrief sessions for child safeguarding can improve the mental wellbeing of staff. However, the sessions need to be held face-to-face, and a clear objective that aligns with staff expectations must be established before the session. References: RCPCH. Child protection and safeguarding | RCPCH [Internet]. [cited 2022 Jan 26]. Available from: https://www.rcpch.ac.uk/key-topics/child-protection Newman J, Vasey J. Exploring support systems for nurses involved with safeguarding children. Nursing children and young people [Internet]. 2020 Mar 12 [cited 2022 Jan 26];32(2):30–7. Available from: https://pubmed.ncbi.nlm.nih.gov/31930889/ Weiss M, Kolbe M, Grote G, Spahn DR, Grande B. Why didn't you say something? Effects of after-event reviews on voice behaviour and hierarchy beliefs in multi-professional action teahttps://doi.org/101080/1359432X20161208652 [Internet]. 2016 Jan 2 [cited 2022 Jan 26];26(1):66–80. from: https://www.tandfonline.com/doi/abs/10.1080/1359432X.2016.1208652 Tannenbaum SI, Cerasoli CP. Do team and individual debriefs enhance performance? A meta-analysis. Human factors [Internet]. 2013 Feb [cited 2022 Jan 26];55(1):231–45. Available from: https://pubmed.ncbi.nlm.nih.gov/23516804/